Exploring the potential for 'Gene Conservation Units' to conserve genetic diversity in wild populations. Issue 2 (9th May 2021) - Minter, Melissa; O'Brien, David; Cottrell, Joan; Ennos, Richard; Hill, Jane K.; Hall, Jeanette
Abstract: 1. Genetic diversity is important for species persistence and Gene Conservation Units (GCUs) have been implemented for forest trees to protect genetic diversity and evolutionary processes in situ. The Convention on Biological Diversity stipulates the protection of genetic diversity as an Aichi target, and so we explore the potential for GCUs to be implemented more widely. 2. Our global systematic review showed that GCUs are currently implemented primarily for plant species of economic importance (109/158 species studied), but a questionnaire sent to land managers and conservationists (60 U.K. participants) revealed strong support for fully integrating genetic information into conservation management (90% agree), and for creating GCUs for other plant and animal taxa. 3. Using four case studies of U.K. species of conservation importance which vary in genetic threat and population dynamics (two insect species, a fungus and a plant), we highlight that GCU implementation criteria need to be flexible to account for variation in effective breeding population size and geographic extent of target species. The wider uptake of GCUs would ensure that threatened genetic diversity is protected and support evolutionary processes that aid adaptation to changing environments. Abstract : Genetic diversity is important for species persistence and Gene Conservation Units (GCUs) have been implemented for forest trees to protect genetic diversity and evolutionary processes in situ. We explore the potential for GCUs to be implemented more widely and found that GCUs are currently implemented primarily for plant species of economic importance, however we found strong support for creating GCUs for other plant and animal taxa and we suggest GCU criteria for multiple taxa.